2018
DOI: 10.1093/jee/toy039
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Methylation Status of Virulent Diuraphis noxia (Hemiptera: Aphididae) Biotypes

Abstract: Epigenetic modifications provide a means for aphid biotype development that a lack of genetic variation, owing to an anholocyclic reproduction lifecycle, fails to do. Here we present data on the DNA methylation status in four South African Russian wheat aphids (RWA), Diuraphis noxia (Kurdjomov) (Hemiptera: Aphididae) biotypes expressing different levels of virulence against its host, Triticum aestivum L. (Poales: Poaceae, Triticeae). The DNA methylation status of these biotypes was determined through the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Hemimethylated DNA arises during DNA replication, as the newly synthesized daughter strand contains unmodified cytosines (Jeltsch, 2002;Goll and Bestor, 2005). When the levels of 5-hmC were measured using the antibody based method, earlier observations (Breeds et al, 2018) were confirmed, as the levels of 5hmC differed significantly between the aphid biotypes, with SAM much higher than that measured in the less virulent SA1 (p < 0.05; Figure 9).…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…Hemimethylated DNA arises during DNA replication, as the newly synthesized daughter strand contains unmodified cytosines (Jeltsch, 2002;Goll and Bestor, 2005). When the levels of 5-hmC were measured using the antibody based method, earlier observations (Breeds et al, 2018) were confirmed, as the levels of 5hmC differed significantly between the aphid biotypes, with SAM much higher than that measured in the less virulent SA1 (p < 0.05; Figure 9).…”
Section: Discussionmentioning
confidence: 65%
“…However, interestingly the difference between the methylation of the top and bottom strands were significantly more in the more virulent SAM (0.09%), than SA1 (0.02%). This was not an unexpected finding, as biotype SAM was previously found to exhibit the highest level of hemimethylation (at the external cytosine) when its methylation was investigated using the Methylation-Sensitive Amplification Polymorphism (MSAP) technique (Breeds et al, 2018). Hemimethylated DNA arises during DNA replication, as the newly synthesized daughter strand contains unmodified cytosines (Jeltsch, 2002;Goll and Bestor, 2005).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations